Higher order formulations for doubly-curved shell structures with a honeycomb core. (July 2021) - Tornabene, Francesco; Viscoti, Matteo; Dimitri, Rossana; Aiello, Maria Antonietta
Abstract: Anisotropic doubly-curved shells reinforced with a honeycomb core are innovative structures for applications in civil, biomedical, and aerospace engineering. In this context, the homogenization technique represents one of the simplest way for analyzing such complex structures. A proper formulation must be capable to give accurate results for any cell configuration and/or curved shape. In the present work an innovative model is proposed, based on an Equivalent Single Layer (ESL) approach and higher order theories, for an accurate estimation of the vibrational response of plates, panels and shells, whose results are compared with predictions from a classical Finite Element Method (FEM). The work starts with a comparative study performed on aluminum sandwich plates with hexagonal, rectangular and re-entrant cells. Then, a sensitivity analysis evaluates the dynamic response of single- and doubly-curved panels with different cell typologies. The fundamental equations are tackled numerically by resorting to the 2D Generalized Differential Quadrature (GDQ) method. The influence of the kinematic assumptions throughout the thickness on the dynamic response of shells is investigated, accounting for different Representative Volume Element (RVE) deformation effects within the homogenized model. In all the analyses, cell units are analyzed by means of different geometric angles, thin and thick cores, as well as classic and double thickness vertical walls or commercial honeycomb cores. Highlights: The free vibration of doubly-curved shells reinforced with a honeycomb core is investigated. Higher order theoretical models based on an equivalent single layer (ESL) approach. Cells with different angles, thin and thick cores, classic and commercial schemes. The GDQ method is applied to solve the equations of motion directly in a strong form.